Perancangan Trading Card Game sebagai Media Informasi Pengenalan Senjata Tradisional Minangkabau untuk Siswa SMP di Sumatera Barat - Hanum, Zikra; Ariesta, Olvyanda (TSAQOFAH, 2025)
Most students at SMP Negeri 6 Payakumbuh are unfamiliar with the various traditional weapons of the Minangkabau culture, reflecting a lack of interest in local cultural content due to the unavailability of information media tailored to the characteristics and preferences of adolescents. This study aims to design an educational media based on a Trading Card Game (TCG) as an enjoyable and interactive tool for introducing Minangkabau traditional weapons to teenagers. The design approach integrates engaging visual elements, contextual narratives, and interactive features to create a meaningful and relevant learning experience. By adopting a modern game concept popular among adolescents, the TCG is expected to serve as an alternative learning medium that is not only informative but also entertaining, thereby enhancing students’ interest and understanding of local cultural heritage. The study concludes that visual game-based media such as TCG has strong potential as an effective strategy for preserving Minangkabau culture while reinforcing the cultural identity of the younger generation amid the challenges of modernization and globalization.